Sistem Pendukung Keputusan Penentuan Penerima Bantuan Keluarga Miskin Menggunakan Metode Analytical Hierarchy Process - Preference Ranking Organization for Enrichment Evaluation II (AHP-PROMETHEE II) - Reza Rahardian; Nurul Hidayat; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The economic level has a big role in the development of a country. Indonesia is one of the countries with low economic level. Indonesia provides data where the funds will be distributed to a region, one of the Mlandingan District, Situbondo district of East Java province. In the area has been given funds intended for the poor. However, the distribution of funds is not optimal enough because there are still people who are able to receive the assistance. Therefore, this research is done to help solve the problem. By applying the AHP PROMETHEE II method applied to a desktop-based application with 6 criteria used as a reference for obtaining accuracy. The AHP method as a weight and PROMETHEE II is used to sort it to get optimal results. In this research, the test is done by measuring the accuracy level with the result reaching accuracy above 80%. Then the AHP method itself in this study used to find the average actually yields an accuracy value that has no effect because the result is the same, so this test is done to know the accuracy value of PROMETHEE II method.